2022
DOI: 10.1057/s41289-022-00211-y
|View full text |Cite
|
Sign up to set email alerts
|

Resilient university campus in the city in COVID and post-COVID era—recommendations, guidelines, and evidence from research in Italy and Poland

Abstract: The pandemic ‘stay at home’ obligations turned our homes from a place to live to a place to live, work, entertain ourselves and to study. Since March 2020, confinement has had a permanent impact on students’ perception of studying and on academic lifestyle. Most universities continue teaching online, and most academic facilities, such as lecture and seminar halls, student halls, and dormitories, have been abandoned. Some of them form vast areas in cities that play a major role in the urban structure. The autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…In this paper, the authors found that the flexible design of dormitories is a crucial parameter for the pandemic resistance of dormitories to be built in the coming years. In recent studies, Amistadi et al ( 2022 ) also provided similar recommendations and guidelines as this study for a resilient urban college campus in the Covid-19 and post-Covid-19 era. Similar to this study, another study was also conducted in college dormitories in Poland under pandemic conditions.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In this paper, the authors found that the flexible design of dormitories is a crucial parameter for the pandemic resistance of dormitories to be built in the coming years. In recent studies, Amistadi et al ( 2022 ) also provided similar recommendations and guidelines as this study for a resilient urban college campus in the Covid-19 and post-Covid-19 era. Similar to this study, another study was also conducted in college dormitories in Poland under pandemic conditions.…”
Section: Discussionmentioning
confidence: 67%
“…Similar to this study, another study was also conducted in college dormitories in Poland under pandemic conditions. According to Amistadi et al ( 2022 ), the pandemic resiliency is important in planning college buildings to be built in the future. Flexibility is an alternative for planning under pandemic conditions and in terms of flexible use proposals.…”
Section: Discussionmentioning
confidence: 99%
“…To cope with the existing problems in dormitories, especially under the influence of the epidemic, some colleges and universities have evaluated the factors of the space environment on the physical and mental environment and proposed improvement strategies [2]. Amistadi et al argued for turning academic facilities with low usage rates into temporary spaces, such as changing skating rinks to vaccination, for flexible university campus design considering the impacts of COVID-19 [3].…”
Section: Introductionmentioning
confidence: 99%